A young athletes in training football schools in Fortaleza-CE - Rodrigues, Abraham Lincoln de Paula (2016)
Currently you can find several football schools in the city of Fortaleza-CE, thus providing a wide range of work for physical education teachers and former athletes. Therefore, we question the ability of these former athletes act in self-detecting process, selection, training and promotion of athletes in the sport. The study aimed to analyze the training process of athletes in football schools in Fortaleza. Study participants were three coaches in three different football schools of the capital. It was used to collect data for a token participant observation and semi-structured interview. The results showed that only one among the three has a degree in Physical Education and the football schools have an important role in the formation of children. In general, the teacher relationships are characterized according to the type of kindergarten in which it operates. They have found structural differences in measured small schools, even because of their different objectives. It was found that the predominant teaching methodology's applied in schools overall. Thus, it can be concluded that small schools share some aspects in common and other distinguished, such as the qualification of teachers, the physical structures, the concern with the social training of the athletes, and the strengthening of citizenship through sport. However, it is important that these similarities and differences are analyzed within the context to which the institution is located, taking into account your objectives.